A preliminary study on helminths detected in red foxes (Vulpes vulpes) in Bingol Province of Türkiye: morphological and molecular approaches - Kilinc, Seyma Gunyakti; Kesik, Harun Kaya; Celik, Figen; Simsek, Sami (Bmc, 2025)
BackgroundRed foxes (Vulpes vulpes) are hosts to a large number of endoparasites, some of which are zoonotic. This study was carried out to identify and molecularly characterise intestinal helminths in foxes in Bingol province, eastern T & uuml;rkiye. For this purpose, carcasses of 15 red foxes that died as a result of traffic accidents in Bingol province were obtained. Parasite material obtained from the intestines was identified according to its morphological characteristics, and complete gDNA was isolated from each individual parasite samples. A 446 bp fragment of the mitochondrial cytochrome c oxidase subunit 1 (mt-CO1) gene was amplified using PCR. Subsequently, a unidirectional sequence analysis was conducted.ResultsThe mt-CO1 gene region of a total of 8 helminth species was successfully sequenced and identified by BLAST searches. One trematode (Alaria alata), five cestodes (Dipylidium caninum, Joyeuxiella sp., Taenia hydatigena, Mesocestoides litteratus, Mesocestoides sp.), one nematode (Toxascaris leonina) and one acanthocephalan (Macracanthorhynchus hirudinaceus) species were identified. Phylogenetic and haplotype analyses were performed on the obtained Mesocestoides spp. sequences. Haplotype analysis of Mesocestoides litteratus isolates revealed 22 haplotypes Mesocestoides.ConclusionThese findings are important to draw attention to the wild circulation of some zoonotic helminths.
Keywords: Red Fox; Helminth; Sequence; Haplotype; T & uuml;rkiye